The Need National Ag Research Has for Communications Support - K. Robert Kern; R. Katherine Jones (Journal of Applied Communications, 1984)
When you set out to describe a "national agricultural research system," your situation has a lot in common with that described in rhyme by a minor poet of the nineteenth century